Developing effective vocabulary teaching techniques to improve vocabulary learning processes in the bilingual system of preparatory school Florida (public school) - Macías Anguiano, Yanet Estefany (Facultad de Filosofía y Letras, 2019)
The purpose of this study is to improve vocabulary learning processes of a foreign language throughout developing effective vocabulary teaching techniques. Chapters written here are about the problems some teachers face when teaching new vocabulary of a foreign language. This thesis mentions important background, proposals, objectives and teaching techniques that improve the process of teaching a foreign language. First, it is show: the problem statement observed when learning a foreign language; second, literary review that emphasizes a variety of some effective vocabulary teaching techniques; third, the methodology used in this study: Action Research in which the study focuses more on English language teachers’ procedures than learners. The procedure of this study is analyzed by observation instruments, rubrics, field notes and listening tracks which determined that English language teachers that applied this study’s proposal did not know the existence of some vocabulary teaching techniques even though, the effective manner to apply them. Those effective vocabulary teaching techniques develop and facilitate both the processes of teaching vocabulary of a foreign language and the processes of learning it. Effective vocabulary teaching techniques overcome traditional processes of learning new vocabulary.